ADMINISTRATIVE LAW — A TOOL FOR SOCIAL JUSTICE AND TRANSFORMATIVE CONSTITUTIONALISM: THE IMPLICATIONS OF MELANI V THE CITY OF JOHANNESBURG (The Pretoria Student Law Review, 2021)
This case note will consider the decision of the High Court in the case Melani v City of Johannesburg.1 I ask whether the Court’s decision is in accordance with progressive substantive aspirations of the Constitution of the Republic of South Africa, 1996.2 In particular, I consider whether the Court’s decision was overly formalistic, whether it met with the requirements of transformative constitutionalism within the context of administrative law and whether the decision furthered social justice. I will start with a brief summary of the facts, the legal question and the decision of the Court in section 2. Section 3 will follow with a consideration of the notion of transformative constitutionalism regarding adjudication within the context of administrative law and social justice. An analysis of whether the Court did in fact further transformative constitutionalism will be discussed in section 4. Finally, I will conclude my discussion in section 5.
Keywords: Melani v City of Johannesburg; case note; High Court; transformative constitutionalism; administrative law; social justice